Does Country Of Origin Matter? A Study In Malaysian Consumer Perception Towards Domestic And Foreign Apparel Brands - Khow, Shi Hui (2003)
Three questionnaires are prepared which carries different information cue(s) respectively with the purpose in investigating different consumer perceptions engendered across three circumstances and their perceptions toward four respective apparel brands under each case. There are total 135 respondents participated in this study. Four apparels brands studied are Padini, Malaysia brand; Giordano, Hong Kong brand; Benetton, Italy brand and Levi’s, US brand. The finding reflects Malaysia consumer do matter of country of origin as they show different perceptions as well as perceived expensiveness when they are presented with different information cue(s). This is notably for Padini, the Malaysia brand and Benetton, Italy brand. Whereas, no obvious effect is detected in Giordano, Hong Kong brand and marginal for Levi’s, US brand. Generally, Malaysia brands are being negatively evaluated by the consumers, which obtain the lowest scores on most of the dimensions tested. On the other hand, consumers perceive Padini favourably when the Malaysia identity is not revealed. However, this positive perception holds as well premium in price deteriorating when the country of origin information is exposed. Moreover, the study reflects that demographic variables (gender, age and education level) provide little explanation in the different consumer perception obtained and also Malaysia apparel brands represent the most frequent purchased brands irrespective favourable or unfavourable image obtained. Lastly, the implications of the study and recommendation to Padini are provided.